Movement of a rolling sphere on a horizontal cylinder (Annual of Sofia University St. Kliment Ohridski. Faculty of Mathematics and Informatics, 1995)
Some aspects of the classical problem about rolling sphere on a homogeneous horizontal cylinder are considered in this paper.